Use of Drugs With Risk of Heart Rate-Related Problems is Common in Norwegian Dementia Patients Treated With Acetylcholinesterase Inhibitors: A Prevalence Study Based on the Norwegian Prescription Database - Efjestad, Anne Sverdrup; Ihle-Hansen, Hege; Hjellvik, Vidar; Engedal, Knut; Blix, Hege Salvesen (Frontiers in Pharmacology, 2022)
Background: Drugs commonly prescribed for heart rate control may induce adverse drug reactions in Alzheimer patients treated with acetylcholinesterase inhibitors (AChEIs). We have studied use of drugs with a known risk of Torsades de pointes (TdP) and drugs used to treat Behavioural and Psychological Symptoms of Dementia (BPSD), as well as combination of drugs with a known risk of TdP and drugs with a known heart rate lowering effect, before and after initiating treatment with AChEIs. Methods: The study applied data from the Norwegian Prescription Database for the period 2004-2016. Prescriptions of concomitant use of drugs in persistent use of AChEI was studied in a follow-up period from four years before to two years after AChEI initiation in men and women of two age groups: 37-80 and 81-88 years. Results: A small number of patients were prescribed haloperidol (~1.5% the 2nd year after AChEI initiation), digoxin/digitoxin (~3%) and verapamil (~1.3%), while a substantial proportion were prescribed betablockers (~28%) and citalopram/escitalopram (~17%). Up to 6% of the study population were prescribed both betablockers and citalopram/citalopram in addition to AChEIs, a combination that increased over the follow-up period and was observed most frequently in women in the oldest age group. Conclusions: A large proportion (~44%) of patients treated with AChEIs were prescribed drugs that could cause bradycardic and prolonged time from the start of the Q wave to the end of the T wave (QT interval). Thus, action should be taken to reduce combination of drugs with risk of bradycardia and prolonged QT interval. Medication review on a regular basis could be an option as an important risk-reducing intervention.